2010
DOI: 10.11646/zootaxa.2655.1.5
|View full text |Cite
|
Sign up to set email alerts
|

The nomenclatural status of Rana gaimardii Bory de Saint-Vincent, 1828, and Hyla quoyi Bory de Saint-Vincent, 1828 (Anura, Hylidae)

Abstract: The nomenclatural status of Rana gaimardii Bory de Saint-Vincent, 1828, and Hyla quoyi Bory de Saint-Vincent, 1828 (Anura, Hylidae) are discussed. Rana gaimardii and its combination Hyla gaimardi, a nomen oblitum under Article 23.9.1 of the International Code of Zoological Nomenclature, may be removed from the synonymy of Hypsiboas boans (Linnaeus, 1758) and included in the synonymy of Hypsiboas faber (Wied-Neuwied, 1821) to improve the geographic distribution of both species. Hyla quoyi Bory de Saint-Vincent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
7
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Article 23.9 of the Code allows the "reversal of precedence", that is, that when a senior homonym or synonym has not been used as a valid nomen after 1899 (Article 23.9.1.1) and its junior synonym or homonym has been used as valid for the same taxon in at least 25 works published by at least 10 authors in the immediately preceding 50 years and encompassing a span of not less than 10 years (Article 23.9.1.2), the junior homonym or synonym must be maintained as valid (Article 23.9.1). One of the cases considered by Ohler and Dubois (2018) is the treatment given by Caramaschi and Niemeyer (2010) to the names Hyla prasina Burmeister, 1856 (under the combination Hypsiboas prasinus), and Hyla quoyi Bory de Saint-Vincent, 1828. Caramaschi and Niemeyer (2010) demonstrated that both names refer to the same species and are then subjective synonyms.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Article 23.9 of the Code allows the "reversal of precedence", that is, that when a senior homonym or synonym has not been used as a valid nomen after 1899 (Article 23.9.1.1) and its junior synonym or homonym has been used as valid for the same taxon in at least 25 works published by at least 10 authors in the immediately preceding 50 years and encompassing a span of not less than 10 years (Article 23.9.1.2), the junior homonym or synonym must be maintained as valid (Article 23.9.1). One of the cases considered by Ohler and Dubois (2018) is the treatment given by Caramaschi and Niemeyer (2010) to the names Hyla prasina Burmeister, 1856 (under the combination Hypsiboas prasinus), and Hyla quoyi Bory de Saint-Vincent, 1828. Caramaschi and Niemeyer (2010) demonstrated that both names refer to the same species and are then subjective synonyms.…”
mentioning
confidence: 99%
“…One of the cases considered by Ohler and Dubois (2018) is the treatment given by Caramaschi and Niemeyer (2010) to the names Hyla prasina Burmeister, 1856 (under the combination Hypsiboas prasinus), and Hyla quoyi Bory de Saint-Vincent, 1828. Caramaschi and Niemeyer (2010) demonstrated that both names refer to the same species and are then subjective synonyms. Hyla prasina (=Hypsiboas prasinus) was then a well-established name in the herpetological literature (see below), while Hyla quoyi was considered "insertae sedis" and (without justification) "nomen oblitum" by Frost's (2010) website "Amphibian Species of the World: an online reference" (this website was accessed by Caramaschi and Niemeyer (2010) on 17 June 2010, and this version is no longer available online).…”
mentioning
confidence: 99%
See 3 more Smart Citations